Students’ Attitudes towards the War in Ukraine - Ilona Huszti; Erzsébet Bárány; Márta Fábián (Educational Challenges)
Purpose. Our research has been conducted in a region of Ukraine where no direct military operations have occurred since 24 February 2022. However, we have been living in the shadow of the horrible ongoing war; regular air raid alarms have had negative impacts on people who feel mental constraints: uncertainty, anxiety, anger, despair, disillusionment, and often hopelessness. Thus, the primary aim of our survey was to get deeper insights into the feelings and attitudes of our students towards the war in order to help them process the situation they have been living in.